EFFECT OF PROGRESSIVE MUSCLE RELAXATION EXERCISE BASED ON ARDUINO UNO ON BLOOD SUGAR, CHOLESTEROL AND URID ACID LEVELS IN THE ELDERLY - Eqlima Elfira (Nurse and Health: Jurnal Keperawatan, 2020)
Abstract Background:Objectives: This study aims to determine the effect of progressive muscle relaxation training on blood sugar, choleterol and uric acid levels in the elderly in Medan Sunggal sub-district.Methods: This study was an experimental study with one group by examining blood sugar, cholesterol and uric acid levels before and after progressive muscle relaxation training. The research respondents were 39 elderly people in environmental areas II and III of Medan Sunggal sub-district. Blood sugar, cholesterol and uric acid levels were measured before the first session and after the end of the progressive muscle relaxation training session three times a week for 4 weeks.Results: The results were analyzed by using the Wilcoxon test using spss 26. Blood sugar and cholesterol levels have the same measurement results, while the pre and post measurements of uric acid levels have an increase in value which means that there is an effect of progressive muscle relaxation training on uric acid levels with a p value <0.05. . which means that Ha is accepted means that there is a difference between pre and post progressive muscle relaxation training based on Arduino Uno.Conclusion:Progressive muscle relaxation training only affects uric acid levels and has no effect on cholesterol and blood sugar levels in the elderly.